Convergence, asymmetry and monetary policy in a common monetary area - Dlamini, Dumsile Faith (My University, 2011)
This thesis examined the extent to which there is convergence in inflation rates, interest rates and incomes in the Common Monetary Area (CMA). It also investigated if countries in the area exhibit asymmetric adjustments to aggregate shocks. Based on optimum currency area theory, lack of convergence and the presence of asymmetric adjustments to shocks is likely to pose serious challenges that need to be addressed as the CMA moves towards a fully-fledged monetary union. I formulated and estimated a macroeconomic model to capture the transmission of shocks in the CMA. The model consists of four equations namely; Phillips curve, IS curve, exchange rate and monetary policy rule. The model links the CMA countries via the aggregate demand, inflation and interest rate equations. I simulated the model to assess the economic performance of the smaller countries when subjected to either a single monetary policy rule or country specific monetary policy rules. Such an analysis is used to gauge if a move towards a fully-fledged monetary union will result in higher benefits for the smaller countries. Furthermore, I estimated a structural VAR model based on the theoretical model. The identification restrictions in the VAR are also derived from the model. The analysis confirms monetary convergence, which is supported by the strong evidence of co-movement in interest rates and inflation rates in the CMA. Monetary convergence is an indicator of strong financial sector integration in the area. There is also evidence that inflation in the smaller countries is driven by that of South Africa. This result is mainly attributable to the strong trade links in the area as well as the existing parity between currencies in the area. The results also show that countries in the area are likely to face asymmetric shocks based on their composition of exports as well as the low correlation of growth rates. However, this asymmetry does not mean that countries cannot move towards iii creation of a fully-fledged monetary union, but rather that the existing asymmetries should be considered seriously by ensuring that other adjustment mechanisms are put in place. Extending the analysis to the SADC region shows that this region exhibits weak monetary convergence even though the poor countries show some form of real convergence with South Africa. Simulations from the VAR model show a price puzzle for Swaziland and South Africa but it is not prolonged. Based on the analysis the study concludes that a monetary union is possible in the CMA and is likely to be less costly. However, the evident asymmetries call for gradual step by step phasing in of the monetary union.
Keywords: Monetary union; Convergence; Asymmetry; Monetary policy